2012
DOI: 10.1085/jgp.201210894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle length on cross-bridge kinetics in intact cardiac trabeculae at body temperature

Abstract: Dynamic force generation in cardiac muscle, which determines cardiac pumping activity, depends on both the number of sarcomeric cross-bridges and on their cycling kinetics. The Frank–Starling mechanism dictates that cardiac force development increases with increasing cardiac muscle length (corresponding to increased ventricular volume). It is, however, unclear to what extent this increase in cardiac muscle length affects the rate of cross-bridge cycling. Previous studies using permeabilized cardiac preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 53 publications
(78 reference statements)
9
41
1
Order By: Relevance
“…In our study, twitch tensions decreased dramatically while contracture tensions were not (muscles from Figures 1 and 2) or only slightly affected (muscles from Figure 3). This is in agreement with our previous report where we showed that the contracture tensions in rat cardiac trabeculae are stable over time at 4 Hz and 37 °C (Milani-Nejad et al 2013). It is thought that a high extracellular K + concentration during this type of contracture induces slow membrane depolarization, activation of calcium channels, and influx of calcium which in turn activates the myofilaments.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In our study, twitch tensions decreased dramatically while contracture tensions were not (muscles from Figures 1 and 2) or only slightly affected (muscles from Figure 3). This is in agreement with our previous report where we showed that the contracture tensions in rat cardiac trabeculae are stable over time at 4 Hz and 37 °C (Milani-Nejad et al 2013). It is thought that a high extracellular K + concentration during this type of contracture induces slow membrane depolarization, activation of calcium channels, and influx of calcium which in turn activates the myofilaments.…”
Section: Discussionsupporting
confidence: 94%
“…This solution was bubbled with 95% O 2 /5% CO 2 where the buffering system results in a pH of 7.4. Trabeculae were isolated from the right ventricle and mounted horizontally in a custom made setup as previously described(Milani-Nejad et al 2013). Muscle were stimulated at 20% over theshhold voltage, using 2 ms bipolar pulses, typically ~5 V. The perfusion solution during experiments was changed to a modified Krebs-Henseleit solution without (BDM) and containing 2 mM CaCl 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations